Pengaruh Variabel Putaran (RPM) terhadap Temperatur Gas Buang Mesin Penggerak Utama Type MAN B&W 31990 KW pada Kapal Kontainer - Lilik Budiyanto; Sugeng Haryadi (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2023)
The research conducted is an analysis of the effect of the main engine rotation (main engine) which tends to change during operation on the exhaust temperature of the main engine on a container ship with a weight of 35981GT. We conducted this research on a container ship KM SPIL Citra PT Salam Pacific Indonesia route during a cruise from Balik Papan Port, East Kalimantan to Bitung Port, North Sulawesi. The purpose of this research is to understand and find out how the main engine speed is determined accordingly so that the main engine exhaust gas is stable and not too high which causes the main engine performance decrease. The test is carried out when the ship is sailing in the middle of the sea in full away condition, the main propulsion engine (main engine) operates at 0.52 Rpm to 57 Rpm with an average running hour for each round of 4 hours. The maximum exhaust gas temperature obtained is 260 C. and the minimum temperature obtained is 230 C with an average temperature of cooling seawater and constant engine room temperature. The conclusion is known that the higher the main engine rotation, the higher the exhaust gas temperature of the main engine so that it is necessary to pay attention to the maximum Rpm limit of the engine so that high temperatures do not occur.